Trade Facilitation Provisions in Regional Trade Agreements: Discriminatory or Non-discriminatory? - Innwon Park; Soonchan Park (East Asian Economic Review (EAER), 2016)
The RTAs with trade facilitation provisions have been expected to generate a larger net trade-creating effect and complement the discriminatory feature of RTAs but have yet to be empirically proven. Recognizing the limitations of existing studies, we conducted a quantitative analysis on the effects of RTAs with and without trade facilitation provisions on both intra- and extra-bloc trade by using a modified gravity equation. We applied the Poisson Pseudo-Maximum Likelihood (PPML) estimation with time varying exporter and importer fixed effect method to panel data consisting of 45,770 country pairs covering 170 countries for 2000-2010. We found that the trade facilitation provisions in existing RTAs are non-discriminatory by generating more intra- and extra-bloc trade in general. In particular, we found that the trade effects of RTAs in the APEC region are much stronger than the general case covering all RTAs in the world. In addition, as we control the trade effect of a country's trade facilitation, which is ranked by the World Bank's logistic performance index, RTAs consisting of trade facilitation provisions are discriminatory for trade in final goods and non-discriminatory for trade in intermediate goods. Overall, we endeavor to "explain," instead of "hypothesizing," why most of the recent RTAs contain trade facilitation provisions, especially in light of the deepening regional interdependence through trade in parts and components under global value chains and support the necessity of multilateralizing RTAs by implementing non-discriminatory trade facilitation provisions.
Keywords: C23; F15; O53; 330; Regional Trade Agreements; Trade Facilitation Provisions; Trade Effect; Gravity Equation; APEC